Pengaruh Promosi, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Batik Di UMKM Gaya Batik Unggul Solo Baru Kecamatan Grogol Sukoharjo - Natasia Tirsa Amanda; Sumaryanto Sumaryanto; Retno Susanti (CV. ITTC INDONESIA, 2025)
The purpose of this study is to determine the significance of the influence of promotion, price and product quality on the purchase decision of batik products in MSMEs Gaya Batik Unggul Solo Baru, Grogol District, Sukoharjo Regency. This study uses a survey method, the types of data used are qualitative data and quantitative data, the data sources used are primary data and secondary data. The number of samples studied was 69 people. The sample size was calculated using Leedy's formula. The sampling technique uses accidental sampling. Data collection methods used: questionnaires and documentation. The data analysis techniques used were validity test, reliability test, classical assumption test, multiple linear regression analysis. The results of the study concluded that promotion, price and product quality have a significant effect on the purchase decision of batik products in MSMEs Gaya Batik Unggul Solo Baru, Grogol District, Sukoharjo Regency. The results of the determination coefficient obtained the result that the contribution of the influence given by the variables of promotion, price and product quality on the decision to purchase batik products in MSMEs Gaya Batik Unggul Solo Baru, Grogol District, Sukoharjo Regency was 78.6% while the remaining 21.4% was influenced by other factors outside the variables studied, such as brand image, service quality, word of mouth and so on.